Recent trends in SST, Chl-a, productivity and wind speed in upwelling and open ocean areas in the Eastern North Atlantic subtropical gyre - Siemer, Julian (2020)
The global upper ocean has been warming during the last decades accompanied with a chlorophyll-a (Chl-a) and productivity decrease. Whereas subtropical gyres show the same trends, Eastern Boundary Upwelling Systems (EBUS), are thought to increase in productivity due to increased trade winds. This study intends to analyze recent trends in sea surface temperature (SST), Chl-a, net primary production (NPP) and meridional wind in the North Atlantic subtropical gyre (NASE) in order to examine if the global trends can be detected in open ocean and upwelling areas and how the Chl-a concentration and productivity respond to changes in SST and meridional wind. Daily and monthly satellite data of SST, Chl-a, NPP and meridional wind of the last 15-40 years were examined to calculate mean trends in four upwelling areas in the Canary upwelling system along Northwest Africa, Portugal and Spain and four open ocean areas including the oceanic areas around the Azores, Madeira and the Canary Islands. The results of this study show that open ocean and upwelling areas in the NASE are warming at different rates (+0.15 to +0.27 °C dec-1 and +0.066 to +0.14 °C dec-1, respectively), Azores being the area with the highest SST increase (+2.70 °C per century). Moreover, a general Chl-a and NPP decrease, most evident in the permanent upwelling areas (Chl-a: -0.31 mg m-3 dec-1; NPP -92.0 mg C m-2 day-1 dec-1) was detected. Similarly, it was found that the permanent upwelling area has become 28 days less productive in the last two decades. The results also highlight an expansion of the oceanic desert area (Chl-a<0.07 mg m-3) of 5 to 10%, and an increase in unproductive days of up to 84 days in the last 20 years in the open ocean. The increase in upwelling favorable wind direction days (27-40 days in the last 30 years) and meridional wind speed (+0.061 to +0.27 m s-1 dec-1) support Bakun’s upwelling intensification hypothesis. Conversely, some smaller areas inside upwelling boxes also exhibit cooling which locally contradicts Bakun’s ...